Barriers and Facilitators for the Use of NURSING Bedside Handovers: Implications for Evidence‐Based Practice. Issue 4 (15th July 2019) - Malfait, Simon; Eeckloo, Kristof; Van Biesen, Wim; Van Hecke, Ann
Abstract: Background: Previous studies on bedside handovers have identified nurse‐related barriers and facilitators for implementing bedside handovers, but have neglected the existing ward's nursing care system as an important influencing factor. Aims: To determine the association between the existing nursing care system (i.e., decentralized, two‐tier, or centralized) on a ward and the barriers and facilitators of the bedside handover. Methods: Structured individual interviews ( N  = 106) on 14 nursing wards in eight hospitals were performed before implementation of bedside handovers. The structured interview guide was based on a narrative review. Direct content analysis was used to determine the nursing care system of a ward and the degree to which barriers and facilitators were present. Pearson's Chi‐square analysis was used to determine whether there were associations between the nursing care systems concerning the presence of barriers and facilitators for implementing bedside handovers. Results: Twelve barriers and facilitators were identified, of which three are new to literature: the possible loss of opportunities for socializing, collegiality, and overview; head nurse's role; and role of colleagues. The extent to which barriers and facilitators were present differed across nursing care systems, with the exception of breach of confidentiality (barrier), and an existing structured handover (facilitator). Overall, nurses working in decentralized nursing care systems report fewer barriers against and more facilitators in favor of using bedside handovers than nurses in two‐tier or centralized systems. Linking Evidence to Action: Before implementing bedside handovers, the context of the nursing care system may be considered to determine the most effective process to implement change. Based on these study findings, implementing bedside handovers could be more challenging on wards with a two‐tier or centralized care system.